Modulation of Electrochemical Nitrogen Reduction by Ionic Liquids on mos2 Electrodes - Ruiz-Leon, D; Ruiz-Leon, D (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The electrochemical reduction of nitrogen (N2) was systematically evaluated using carbon-based electrodes modified with molybdenum disulfide (MoS2) and ionic liquids (ILs). MoS2 was synthesized via a hydrothermal method, yielding a nanoflower morphology with nanosheet-like surfaces, as observed by field-emission scanning electron microscopy (FESEM) and High-Resolution Transmission Electron Microscopy (HRTEM). X-ray diffraction (XRD) confirmed the formation of hexagonal-phase MoS2 (H-MoS2). Inks were formulated using MoS2 and four ionic liquids containing the bis(trifluoromethylsulfonyl)imide ([TFSI]) anion and subsequently deposited onto carbon paper electrodes. Electrochemical characterization revealed that the presence of ILs suppressed the faradaic current associated with the hydrogen evolution reaction (HER) while simultaneously enhancing the faradaic response corresponding to the nitrogen reduction reaction (NRR). This behavior is attributed to the formation of a hydrophobic interface and improved N2 adsorption facilitated by the ILs. Electrolysis experiments demonstrated that both faradaic efficiency and ammonia yield increased as a function of the nonpolar chain length in the IL cation. Specifically, MoS2 exhibited a performance enhancement from 1.54 % and 0.729 mu g h-1 cm-2 to 9.31 % and 6.76 mu g h-1 cm-2, respectively, when using the ionic liquid [BMPyrr][TFSI]. This evidence underscores the potential of ILs in suppressing HER and enhancing the selectivity and efficiency of electrodes for electrochemical N2 reduction.